Implications of mechanosensitive ion channels in the pathogenesis of osteoarthritis: a comprehensive review - Zhang, Yuelong; Zhuang, Huangming; Ren, Xunshan; Zhou, Panghu (Frontiers in Cell and Developmental Biology, 2025)
Osteoarthritis (OA) is the predominant cause of joint pain and limited mobility in older people, and its prevalence is increasing as the population ages. Given the lack of effective therapeutic interventions, the disability rate associated with OA is a staggering 53%, which significantly affects the wellbeing of those affected and represents a significant social and family financial burden. Consequently, OA has emerged as a pressing social and public health concern globally. Various forms of mechanical strain, such as dynamic compression, fluid shear, tissue shear, and hydrostatic pressure, serve as crucial physical stimuli perceived by chondrocytes. Recent studies indicate that aberrant mechanical loading represents a fundamental risk factor for OA. Upon exposure to mechanical loading, chondrocytes translate mechanical cues into chemical signals primarily via mechanosensitive ion channels, resulting in alterations in cartilage metabolism. Numerous studies have demonstrated the significance of mechanosensitive ion channels in the pathogenesis of OA, suggesting that therapeutic interventions targeting these channels on chondrocytes may offer potential benefits.